PENJADWALAN & PERLAKUAN PERAWATAN MESIN DISTILASI MENGGUNAKAN METODE RELIABILITY CENTERED MAINTENANCE II DAN IMPLEMENTASI APLIKASI ODOO - Oktavian, Fariidz Tri (2023)
UPN Veteran Jakarta's PPIC Laboratory has plans to reactiving a Distillation Machine which has not been used for 2 years, to learning laboratory. So that'snecessary to plan the scheduling and maintenanc machine, but several failures are found in each engine component such as steam leaks, corrosion, failure of the shape components, which causes the machine decrease in engine performance & product contamination. So, researchers need to make schedule & action plan machine maintenance based on existing failures, encouraging the recall of critical components using FMEA, action plan and maintenance schedule creation using the RCM II method and implementation of the Odoo application to make digital schedule that can be accessed together in operational laboratories. The result, it was found that the distillation machine had 2 critical components, namely the boiler & the distillator tube with each RPN value of 175& 130 and the treatment for the boiler is Scheduled on Condition Task and the distillator tube is Scheduled on Condition Task & Scheduled Restoration Task for suggesting inspection time intervals every 32 hours for boiler components and 64 hours intervals for distillator tubes calculated in the cumulative calculation plus digital scheduling using odoo in this research on maintenance & repairs management modul.